2005
DOI: 10.1128/jb.187.2.707-715.2005
|View full text |Cite|
|
Sign up to set email alerts
|

A Synonymous Mutation in Yersinia enterocolitica yopE Affects the Function of the YopE Type III Secretion Signal

Abstract: Yersinia spp. inject virulence proteins called Yops into the cytosol of target eukaryotic cells in an effort to evade phagocytic killing via a dedicated protein-sorting pathway termed type III secretion. Previous studies have proposed that, unlike other protein translocation mechanisms, Yops are not recognized as substrates for secretion via a solely proteinaceous signal. Rather, at least some of this information may be encoded within yop mRNA. Herein, we report that the first seven codons of yopE, when fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The results have suggested in certain cases that specific regions in the N-terminal region of effectors and translocators constitute the secretion signal (Sory et al, 1995; Lloyd et al, 2001; Amer et al, 2011), whereas in other cases it has been suggested that the secretion signal is encoded in the mRNA sequence (Anderson and Schneewind, 1997; Ramamurthi and Schneewind, 2005). However, secretion is a complex process and targeting is just the first step of it.…”
Section: Discussionmentioning
confidence: 99%
“…The results have suggested in certain cases that specific regions in the N-terminal region of effectors and translocators constitute the secretion signal (Sory et al, 1995; Lloyd et al, 2001; Amer et al, 2011), whereas in other cases it has been suggested that the secretion signal is encoded in the mRNA sequence (Anderson and Schneewind, 1997; Ramamurthi and Schneewind, 2005). However, secretion is a complex process and targeting is just the first step of it.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, two synonymous substitutions, each at isoleucine codon 3, abrogated the function of yopE and yopQ minimal secretion signals. When introduced into full-length yopE , such single nucleotide substitutions significantly reduce YopE injection into tissue culture cells, although substrate recognition was not completely blocked (Ramamurthi and Schneewind, 2005). In yopE , the AUA and AUU nucleotide triplets of Ile codon 3 promote secretion signalling, whereas AUC does not (Ramamurthi and Schneewind, 2005).…”
Section: The Mrna Signal Hypothesismentioning
confidence: 99%
“…Even the tolerance of secretion signals to frameshift mutations has limits. Mapping the minimal secretion signal of yopE and yopQ identified the first seven or 10 codons as functional elements (Ramamurthi and Schneewind, 2005). However, frameshift mutations of these minimal secretion signals abrogated function, although that initiation of the encoded hybrids into the type III pathway could be restored by fusion of downstream yopE or yopQ codons (7-15 codons).…”
Section: The Mrna Signal Hypothesismentioning
confidence: 99%
“…For example, many mRNAs encoding inner membrane proteins are preferentially localized at the membrane and this localization can be mediated in a translation-dependent manner during synthesis and secretion of N-terminal signal peptides. However, for certain mRNAs encoding inner membrane proteins or secreted effectors, it has been reported that signals within the mRNA itself are instead required for localization/secretion or that the mRNAs have multiple localization signals, including RNA sequence-based and those encoded in the N-terminal peptide amino acid sequence (10, 72, 74, 147). It remains to be seen how many bacterial mRNAs have a eukaryotic-like RNA zip-code, and what the sequence- and/or structural features of these elements are.…”
Section: Open Questions and Future Challengesmentioning
confidence: 99%